COMPROMISED PREFRONTAL STRUCTURE AND FUNCTION ARE ASSOCIATED WITH SLOWER WALKING IN OLDER ADULTS. (11th November 2018) - Wooten, T; Poole, V; Iloputaife, I; Esterman, M; Lipsitz, L
Abstract: Walking speed is one of the strongest predictors of health outcomes in older adults, and has been associated with falls, morbidity, and mortality. Slow walking has also been linked to reduced executive functioning and altered functional brain integrity. Specifically, our previous work has demonstrated that reduced activation of the executive network during a working memory (n-back) task is associated with slow walking speed in a cohort of older adults from the Maintenance of Balance, Independent Living, Intellect and Zest in the Elderly of Boston Study (MOBILIZE Boston Study). However, the simultaneous influence of underlying white matter integrity on executive functioning, executive network brain activation, and walking speed is unknown. Thus, we used diffusion weighted imaging and fMRI during the n-back task to assess associations between executive network structure, function, and walking speed. Whole-brain tract-based spatial statistics (TBSS) were used to identify regions of white matter microstructural integrity that were associated with slow walking speed. The integrity of these regions, quantified by fractional anisotropy (FA), was then correlated with n-back performance and executive network activation. Lower FA in the right superior longitudinal fasciculus, right anterior thalamic radiation, and the forceps minor of the corpus callosum was significantly associated with slow walking speed. Low FA in these frontal white matter regions was further associated with poor n-back performance (response speed) and reduced executive network activation. These findings suggest that microstructural damage to the right frontal white matter may partially account for altered executive network activation and slow walking speed in older adults.